A Proposed Legal Framework On The Extraction And Consumption Of Outer Space Resources - Gordon, Melissa M. (UND Scholarly Commons, 2012)
The future of space exploration endeavors depends highly on the utilization of in-situ resources. Large scale exploration road maps take advantage of local resources to reduce mission costs and enable the growth of revolutionary self-sufficient technologies to prolong mission duration and reach beyond current destinations. The major space treaties included limited provisions on space resource utilization in terms of excavation and consumption. A natural resource can be extracted from its place of origin with limited restriction on the quantity and method of use. To address the risk of ecological damage, resource appropriation, and impending disputes, claims, and decrees regarding resource utilization, a comprehensive analysis is performed on the legal doctrines governing activities in outer space, the environmental protocol of Antarctica, the principles of the high seas, and a case study on resource appropriation. An analysis of the aforementioned doctrines concludes: 1) the need to provide an international authority with the power to act when claims and disputes of international cooperation and consultations fail and 2) the need to establish a protocol on environmental protection to the Outer Space Treaty to ensure peaceful and orderly development of our celestial bodies during scientific and commercial activities involving resource utilization.